Making Asian American film and video : histories, institutions, movements - Okada, Jun, 1973- (Asian American studies today., 2015)
The words "Asian American film" might evoke a painfully earnest, low-budget documentary or family drama, destined to be seen only in small film festivals or on PBS (Public Broadcasting Service). In her groundbreaking study of the past fifty years of Asian American film and video, Jun Okada demonstrates that although this stereotype is not entirely unfounded, a remarkably diverse range of Asian American filmmaking has emerged. Yet Okada also reveals how the legacy of institutional funding and the "PBS style" unites these filmmakers, whether they are working within that system or setting themsel